CLAUSA Is a MYB Transcription Factor That Promotes Leaf Differentiation by Attenuating Cytokinin Signaling - Bar, Maya; Israeli, Alon; Levy, Matan; Ben Gera, Hadas; Jiménez-Gómez, José M; Kouril, Stepan; Tarkowski, Petr; Ori, Naomi (The Plant cell, 2016)
Leaf morphogenesis and differentiation are highly flexible processes, resulting in a large diversity of leaf forms. The development of compound leaves involves an extended morphogenesis stage compared with that of simple leaves, and the tomato (Solanum lycopersicum) mutant clausa (clau) exposes a potential for extended morphogenesis in tomato leaves. Here, we report that the CLAU gene encodes a MYB transcription factor that has evolved a unique role in compound-leaf species to promote an exit from the morphogenetic phase of tomato leaf development. We show that CLAU attenuates cytokinin signaling, and that clau plants have increased cytokinin sensitivity. The results suggest that flexible leaf patterning involves a coordinated interplay between transcription factors and hormones.
Keywords: Solanum lycopersicum; Plant Proteins; geneticky modifikované rostliny; Cytokinins; signální transdukce; Plant Leaves; Signal Transduction; mutace; transkripční faktory; Mutation; Plants, Genetically Modified; Transcription Factors; rostlinné proteiny; regulace genové exprese u rostlin; listy rostlin; cytokininy; Gene Expression Regulation, Plant